Peranan Pelaksanaan "Key Performance Indicators" (KPI) Dalam Penilaian Prestasi di Organisasi Sektor Awam: Kajian Kes di Bahagian Penilaian Majlis Bandaraya Alor Setar (MBAS) - Qadarsih (2012)
One of the functions of the public sector is organizing the public service which is a general form of government task for welfare the society. Public service is a main milestone for government. Hence, government provides the guidelines by using key performance indicators to improve quality of care. Thus, this research has been done to understand the role of KPIs implementation to measure performance in a public sector organization. This research was done in the Assessment Department in MBAS. This research was a qualitative descriptive which used interviews as a method to get the data. The informant in this study was the staff member of the Assessment Department in MBAS to understand the role of KPIs implementation and the factors hinder in the implementation of KPIs. The result of this study shows that team work and work environment are the dominant factors that hamper to implement the KPIs. In this research, some suggestions were given that related to the role of KPIs implementation to improve the quality of performance both staff and organization.